Cultural value discrepancies, strategic positioning and integrated identity: American migrants' experiences of being the Other in mainland China. Issue 1 (2nd January 2021) - Liu, Yang; Kramer, Eric
ABSTRACT: Focusing on 35 American migrants' experiences in mainland China, this study provides a new conceptual understanding of international migrants' Other -identity formulated in and through intercultural encounters. Guided by grounded theory, this study demonstrates that American migrants' Otherness was frequently triggered by their divergences from Chinese cultural values' emphasis on individuals' conformity to interdependence, group interests, group cohesiveness, homogeneity and unequally distribution of power and status within a social structure. As the Other in mainland China, American migrants adapted themselves to Chinese society via diverse strategic positioning, which eventually contributed to the differential formation of an integrated identity during immigration.